A multicentre observational study on neonates exposed to SARS-CoV-2 in China: the Neo-SARS-CoV-2 Study protocol. Issue 7 (22nd July 2020) - Xiao, Tiantian; Xia, Shiwen; Zeng, Linkong; Lin, Guang; Wei, Qiufen; Zhou, Wei; Zhuang, Deyi; Chen, Xiao; Yi, Bin; Li, Long; Mi, Hongying; Yin, Zhaoqing; et al.
Abstract : Introduction: An outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) occurred in Wuhan, China starting in December 2019. Yet the clinical features and long-term outcomes of neonates with SARS-CoV-2 exposure are lacking. The purpose of this study is to describe the clinical course and prognosis of the neonates exposed to SARS-CoV-2. Methods and analysis: This is a multicentre observational study conducted at the designated children and maternal and child hospitals in the mainland of China. Neonates exposed to SARS-CoV-2 infection will be recruited. The data to be collected via case report forms include demographic details, clinical features, laboratory and imaging results, as well as outcomes. Primary outcomes are the mortality of neonates with COVID-19 and SARS-CoV-2 infection of neonates born to mothers with COVID-19. Secondary outcomes are the birth weight, premature delivery and neurological development of neonates exposed to SARS-CoV-2. The neurological development is assessed by the Chinese standardised Denver Developmental Screening Test at the corrected age of 6 months. Ethics and dissemination: This study has been approved by the Children's Hospital of Fudan University ethics committee (No. (2020)31). The study findings will be disseminated in peer-reviewed journals and presented at national and international conferences in order to improve the understanding of the clinical course among neonates exposed to SARS-CoV-2 and to provide evidence-based treatment and prevention strategies for this group. Trial registration number: NCT04279899 .